Perspectives of Stakeholders from Indian Secondary Schools about Conducting Board Examinations Twice a Year - Yadav, Karuna; Mahananda, Poulastya; Sethy, Rasmirekha; Singh, Sukhavinder; Mohalik, Ramakanta (Randwick International of Education and Linguistics Science Journal, 2025)
Board examinations play a vital role in the academic journey of students and significantly influence teachers' responsibilities. However, the current examination system has been criticized for contributing to student stress, anxiety, inconsistent grading, and over-reliance on rote learning, which has led to a decline in public trust. To address these challenges, the introduction of conducting board examination twice a year, recommended by the National Education Policy (NEP) 2020 and National Curriculum Framework-School Education (NCF-SE)2023 represents a major reform in the education system. This study investigates the perspectives of stakeholders on conducting board examinations twice a year in Khurda district, Odisha, India. A descriptive research design and survey method were employed, with a randomly selected sample consisting of schools, head-teachers, teachers, and students. The total sample comprised 10 head-teachers, 100 teachers, and 200 students. The findings indicate that 78.18% of participants believe board examinations twice a year would reduce student stress, 81.81% agree it provides better preparation opportunities, and 86.36% think frequent and timely feedback fosters academic growth. However, 50% of stakeholders expressed concerns about increased teacher workload. Students supported conducting board examinations twice a year, believing it would encourage consistent study habits, reduced stress, and fostered a growth mindset. However, concerns were raised about resource inequalities benefiting well-supported students. These results underscore the potential benefits and challenges of implementing board examinations twice a year, offering valuable insights for policymakers and educators in shaping future examination reforms.